2013
DOI: 10.3724/sp.j.1263.2012.08141
|View full text |Cite
|
Sign up to set email alerts
|

Atrial fibrillation in the elderly: the potential contribution of reactive oxygen species

Abstract: Atrial fibrillation (AF) is the most commonly encountered cardiac arrhythmia, and is a significant source of healthcare expenditures throughout the world. It is an arrhythmia with a very clearly defined predisposition for individuals of advanced age, and this fact has led to intense study of the mechanistic links between aging and AF. By promoting oxidative damage to multiple subcellular and cellular structures, reactive oxygen species (ROS) have been shown to induce the intra- and extra-cellular changes neces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 70 publications
0
13
0
Order By: Relevance
“…However, whether ROS and mitochondrial dysfunction as result of the ageing process alone are sufficient to produce an arrhythmogenic atrial substrate remain in question. 15 In our study, we observed that among AF patients, those with the mtDNA mutation were older on average. In comparison to their age-matched controls, elderly AF patients still maintained a higher prevalence of mtDNA 4977 - mut .…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…However, whether ROS and mitochondrial dysfunction as result of the ageing process alone are sufficient to produce an arrhythmogenic atrial substrate remain in question. 15 In our study, we observed that among AF patients, those with the mtDNA mutation were older on average. In comparison to their age-matched controls, elderly AF patients still maintained a higher prevalence of mtDNA 4977 - mut .…”
Section: Discussionmentioning
confidence: 60%
“…According to recent studies, the mechanism underlying aging is primarily a progressive decline in mitochondrial function. 15 Leakage of superoxide from the mitochondrial electron transport chain induces oxidative damage and accumulation of damage over time results in mtDNA deletion. 16 , 17 mtDNA 4977 - mut is one of the most common deletion mutations identified in mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…This oxidative stress may produce cardiac electrical activity alterations, damaging ion channels and finally leading to the AF development. (22,23)…”
Section: Discussionmentioning
confidence: 99%
“…In our clinical experience, a good parameter for the occurrence of AF is ageing, which is referred to as an oxidative condition 3 . We have paid special attention to the relevance of oxidative stress in cardiometabolic pathologies.…”
mentioning
confidence: 99%
“…We have paid special attention to the relevance of oxidative stress in cardiometabolic pathologies. Notably, oxidative stress conditions are involved in the pathogenesis of AF 3 4 . Thus, we wonder if some patients had a relatively high red blood cell level (even though it was not at the level of polycytemia), which could have led to oxidative stress.…”
mentioning
confidence: 99%